An Analysis of Islamic Law in Handling Divorce and Its Impact on Children - Pasaribu, Yunita; Aswin, Aswin (El-Sirry: Jurnal Hukum Islam dan Sosial, 2024)
This study aims to analyze the factors that cause divorce from an Islamic perspective and its impact on families, especially children, by emphasizing the importance of maintaining the integrity of the household. This study uses a qualitative approach with a literature study method, examines Islamic teachings on divorce, and identifies factors that cause divorce, such as biological, psychological, moral, economic, and sociological factors. The results show that divorce, although allowed in Islam, is strongly discouraged because of its widespread and negative impact, especially on children who are often the most emotionally and socially disadvantaged. This study recommends the importance of strengthening the values of domestic harmony through family education based on Islamic teachings, conflict management in a peaceful way, and providing counseling for couples facing domestic problems. Thus, divorce can be minimized, and the integrity of the family can be maintained in accordance with Islamic values